2020
DOI: 10.1167/iovs.61.5.48
|View full text |Cite
|
Sign up to set email alerts
|

Association of Age-Related Cataract With Skin Cancer in an Australian Population

Abstract: Ultraviolet radiation from sunlight contributes to age-related cataract and skin cancer. The EPHA2 gene is implicated in both these diseases. The purpose of this study was to determine whether age-related cataract and skin cancer are associated in a cohort of older Australians. METHODS. A cross-sectional study was performed using the Historical Cohort of the Registry of Senior Australians. Individuals aged ≥65 years or aged ≥50 years and of Aboriginal or Torres Strait Islander descent, who had an aged care eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 44 publications
(57 reference statements)
1
13
0
Order By: Relevance
“…e results of active services, service attitude, health education, psychological support, and patients care satisfaction rate in the experimental group were apparently higher than in the control group, demonstrating that medical staff actively and patiently answer all kinds of doubts for patients and assist patients solve various practical problems in the process of implementing the cataract ZhuanBing standards of care in ophthalmology wards. Importantly, health promotion for patients not only strengthens communication between each other but also meets patients' requirements, which helps to reduce medical disputes, improve patients' satisfaction with medical staff and their own image, and increase social benefits [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…e results of active services, service attitude, health education, psychological support, and patients care satisfaction rate in the experimental group were apparently higher than in the control group, demonstrating that medical staff actively and patiently answer all kinds of doubts for patients and assist patients solve various practical problems in the process of implementing the cataract ZhuanBing standards of care in ophthalmology wards. Importantly, health promotion for patients not only strengthens communication between each other but also meets patients' requirements, which helps to reduce medical disputes, improve patients' satisfaction with medical staff and their own image, and increase social benefits [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…After irradiation with 254 nm, about 70% of the basal cells in the skin are negatively affected in their vitality 13 , while almost no pre-mutagenous UV-associated DNA lesions were observed with 222 nm, which can be explained by the higher absorption of 254 nm wavelength by proteins and nucleic acids—being associated with the development of mutations leading to skin cancer 11 , 12 and eye cataracts 14 , 15 . However, high energy UVC radiation ( λ < 245 nm) is strongly absorbed by the stratum corneum (SC), the horny layer that does not contain cell nuclei 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to UV radiation from sunlight has been considered as a risk factor for both skin cancer and cataract. A recent cross-sectional study from Australia demonstrated that the prevalence of skin cancer was higher in patients with cataracts than in those without [ 6 ]. However, there is also conflicting evidence of sunlight exposure as a possible risk factor for cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…Various conditions including hypertension [ 1 ], diabetes mellitus (DM) [ 2 ], Parkinson’s disease [ 3 ], atopic dermatitis [ 4 ], and vitiligo [ 5 ] have been suggested as possible comorbidities of skin cancer, but the relationship between skin cancer and other diseases remains unclear. The eye is another structure commonly exposed to sunlight, and previous studies have indicated a possible association of skin cancer and ocular conditions including cataract [ 6 ], and pterygium [ 7 , 8 ]. However, despite the fact that the skin and eyes are the two organs frequently exposed to the sun, thus sharing ultraviolet (UV) radiation as a risk factor for various skin and ocular diseases, investigations of various ocular comorbidities of skin cancer-based on large samples have rarely been performed.…”
Section: Introductionmentioning
confidence: 99%